Creative Thinking Boost: Discovery Learning and STS Approach for Middle School: Meningkatkan Kemampuan Berpikir Kreatif pada Siswa SMP Melalui Pembelajaran Penemuan dan Pendekatan Sains-Teknologi-Masyarakat - Fitria Eka Wulandari; Fitria Febrianti; Noly Shofiyah (Universitas Muhammadiyah Sidoarjo, 2023)
This research aimed to analyze the impact of Discovery Learning model implementation through a Science-Technology-Society (STS) approach on creative thinking skills among middle school students. A quantitative pre-experimental design with a one-group pretest-posttest method was utilized. The study was conducted on a sample of 14 students from Muhammadiyah 4 Porong Middle School, with the instrument being a test of creative thinking skills. Data were gathered through pretest and posttest scores, analyzed using N-Gain test. The result, an N-Gain score of 0.38, indicated a moderate effect of the Discovery Learning model via the STS approach on the students' creative thinking skills. The skills were divided into four indicators: fluency, flexibility, originality, and elaboration. Post-intervention, fluency exhibited the highest improvement, followed by flexibility and elaboration, while originality showed the least progress. Despite certain limitations in originality and detail-oriented thinking, the study still provided strong evidence for the efficacy of the combined Discovery Learning and STS approach in enhancing students' creative thinking abilities, endorsing its broader application in education settings to foster creativity. Highlights: Discovery Learning model coupled with the Science-Technology-Society (STS) approach moderately improves students' creative thinking skills. Among the four assessed creative thinking indicators, fluency and flexibility displayed significant improvement. Despite the less notable progress in originality, the combined model's overall positive impact endorses its broader application in education settings. Keywords: Discovery Learning, Science-Technology-Society Approach, Creative Thinking Skills, Middle School Education, N-Gain Score